2017
DOI: 10.1016/j.ijrobp.2017.06.323
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Disease and Lifestyle Risk Factors Following Hodgkin Lymphoma: An EORTC Lymphoma Group and GELA Follow-Up Study

Abstract: Prior studies have shown a significantly reduced second-cancer risk in Hodgkin lymphoma (HL) survivors treated with more limited-field radiation therapy (RT), although the impact of RT field size reduction on long-term overall survival (OS) has been unclear. The purpose of this study is to analyze long-term OS by field size. Materials/Methods: An institutional review board-approved retrospective study was conducted using a multi-institutional database of stage I and II HL patients treated 1967-2007 with RT wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Of the whole population, 1990 patients responded to a patient-reported questionnaire (median age at treatment 29 years; median follow-up duration 14 years). The analysis showed that BMI ≥ 30 was not statistically significant as a risk factor for cardiac disease (OR 1.3 95%CI 0.9-1.8) [45]. The quality of this study was intermediate: selection of cases and outcome were good; the main concern/cons regarded the lack of a control group and the self-reported outcome.…”
Section: Bodyweight and Bmi: Does A Controlled Bodyweight Or Adequate...mentioning
confidence: 70%
See 2 more Smart Citations
“…Of the whole population, 1990 patients responded to a patient-reported questionnaire (median age at treatment 29 years; median follow-up duration 14 years). The analysis showed that BMI ≥ 30 was not statistically significant as a risk factor for cardiac disease (OR 1.3 95%CI 0.9-1.8) [45]. The quality of this study was intermediate: selection of cases and outcome were good; the main concern/cons regarded the lack of a control group and the self-reported outcome.…”
Section: Bodyweight and Bmi: Does A Controlled Bodyweight Or Adequate...mentioning
confidence: 70%
“…Among other factors, a BMI > 25 seemed to be associated with a higher risk of coronary heart disease in cHL survivors [30], even if data were not confirmed in a subsequent study [45]. Both studies correlated BMI > 25 with higher risks for the following: hypertension; diabetes mellitus and smoking during the 5 years preceding the diagnosis of coronary heart disease; and factors related to the oncologic therapy, especially a dosedependent mediastinal irradiation [30,45].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation